Literasi Digital dan Tantangan Gaya Berbahasa: Analisis Penggunaan Media Sosial oleh Mahasiswa dalam Diskusi Kelas Online - Marselina Nona Peuhulu; Alasriati Alasriati; Try Try; Gilang Mahdy Saputra Surya; Yeremias Bardi (STIKes Ibnu Sina Ajibarang, 2026)
In today's digital era, social media has become an integral part of everyday life, especially for younger generations such as students. Platforms like Instagram, TikTok, Twitter, and Facebook facilitate fast and interactive communication, but often encourage the use of informal language such as abbreviations or emojis. This contrasts with the demands of the academic world. This study aims to analyze the influence of social media use on students' language styles in the academic world. The research method used was quantitative, namely observation. Observations were conducted to determine students' communication patterns on digital platforms (such as class WhatsApp group chats and comments on social media). The results showed a strong tendency to use slang, non-standard abbreviations, and code-mixing, carried over from social media habits into formal academic contexts. This phenomenon has contributed to the erosion of the boundaries between informal and formal language styles among students. This study concludes the need to strengthen formal language literacy to maintain professional communication in the academic world.